2009
DOI: 10.1089/jamp.2008.0718
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Jet Nebulization and Oxygen Delivery on the Fraction of Inspired Oxygen: An Experimental Model

Abstract: Oxygen delivery through a nasal device during air-driven jet nebulization significantly increases the FiO(2), whereas oxygen-driven jet nebulization dramatically decreases FiO(2) compared with standard oxygen therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 22 publications
0
11
0
1
Order By: Relevance
“…Furthermore, differences in the point of entry of aerosol into humidified/ non-humidified air across the various delivery modalities may also be a contributing factor, where aerosol is entrained in the gas flow in the most efficient manner, thereby avoiding impactional losses within the circuit and patient interface. Clinical studies demonstrate that the connection of a nebulizer to a HFNT circuit enables continuous nebulization, therefore improving efficiency and tolerance of the therapy [20, 28, 29]. Valencia and colleagues recently reported that the use of a nebulizer incorporated into HFNT results in an increased level of comfort and satisfaction compared to the use of a conventional JN in bronchiolitis patients who require HFNT [21].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, differences in the point of entry of aerosol into humidified/ non-humidified air across the various delivery modalities may also be a contributing factor, where aerosol is entrained in the gas flow in the most efficient manner, thereby avoiding impactional losses within the circuit and patient interface. Clinical studies demonstrate that the connection of a nebulizer to a HFNT circuit enables continuous nebulization, therefore improving efficiency and tolerance of the therapy [20, 28, 29]. Valencia and colleagues recently reported that the use of a nebulizer incorporated into HFNT results in an increased level of comfort and satisfaction compared to the use of a conventional JN in bronchiolitis patients who require HFNT [21].…”
Section: Discussionmentioning
confidence: 99%
“…(12) The connection of a nebulizer to the HFT circuit may be considered as a simple solution that may enable continuous nebulization without interrupting HFT, thereby improving the efficiency and tolerance of the overall procedure. (13,14) Nevertheless, several barriers may impede efficient nebulization through HFT circuits. First, aerosol deposition in the HFT circuit may be favored by humidification and high flow rates used in the adult setting in a similar way as observed during mechanical ventilation.…”
Section: Introductionmentioning
confidence: 99%
“…The vast majority of studies have used air- or oxygen-driven pneumatic nebulizers. Oxygen-driven jet nebulization is preferable in the hypoxemic patient, but the expected FiO2 values are low because of the absence of an oxygen reservoir coupled to aerosol masks [114]. With their lower residual volume, ultrasonic nebulizers and vibrating mesh nebulizers have the same efficacy as pneumatic nebulizers and metered dose inhalers used with valved holding chambers [115].…”
Section: Resultsmentioning
confidence: 99%